THE INFLUENCE OF PUBLIC RELATIONS' CONFIDENCE IN COMMUNICATING - Bambang Sunaryo (SEAN Institute, 2020)
This study aims to analyze and understand the influence of a public relations's confidence in communicating. Confidence as an early part of public relations and public speaking activities in communication is very interesting to study, considering that public relations will be built if you have confidence in communication. This study uses the library method in which activities related to the collection of library data from journals, books, and also trusted communication websites related to the influence of a public relations's self-confidence.The confidence of a public relations person is very important because, from that confidence, we can know and easily carry out a communication, both for the public and for ourselves